Penyuluhan Praktek Cuci Tangan Menggunakan Sabun Pada Siswa Sekolah Dasar Negeri 01 Desa Sukamantri Tangerang - Kimsen Kimsen; January Eky Pambudi (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2023)
The habit of washing hands with soap (CPTS) is a healthy behavior scientifically proven to prevent the spread of diseases such as diarrhea, Upper Respiratory Tract Infections (ARI), and flu. Washing hands is an act of cleaning hands and fingers using water or other liquids with the aim of making them clean, part of a religious ritual, or for other purposes. School-aged children are vulnerable to various diseases. The habit of children consuming snacks freely, plus children not washing their hands with soap before eating, will result in various diseases. To avoid this, proper counseling regarding CPTS is needed. Counseling was carried out on August 11 2023 for class I & II students at SDN 01 Sukamantri with a total of 75 students. The method used is counseling and demonstration of washing hands with soap through 7 steps for washing hands with soap. After carrying out outreach activities in the form of education and CTPS demonstrations, results were obtained in increasing students' knowledge regarding the material provided. So it can be concluded that this activity can increase their knowledge of good and correct CPTS. This aims to reduce the number of student absences due to illness caused by diseases.